sigma-Hole Bonding: A Physical Interpretation - Politzer, Peter; Murray, Jane S.; Clark, Timothy (Springer Verlag Kg, 2015)
The anisotropic electronic densities of covalently-bonded Group IV-VII atoms frequently give rise to regions of positive electrostatic potential on the extensions of covalent bonds to these atoms. Through such positive "sigma-holes," the atoms can interact attractively and highly directionally with negative sites such as the lone pairs of Lewis bases, anions, pi electrons, etc. In the case of Group VII this is called " halogen bonding." Hydrogen bonding can be viewed as a less directional subset of sigma-hole interactions. Since positive sigma-holes often exist in conjunction with regions of negative potential, the atoms can also interact favorably with positive sites. In accordance with the Hellmann-Feynman theorem, all of these interactions are purely Coulombic in nature (which encompasses polarization and dispersion). The strength of sigma-hole bonding increases with the magnitudes of the potentials of the positive sigma-hole and the negative site; their polarizabilities must sometimes also be taken explicitly into account.
Keywords: Coulombic interactions; Halogen bonding; sigma-Hole bonding